‘Écraser l’infâme!’: Artists and the Concentration Camp: The Art Collection of the Sachsenhausen Memorial - Kaumkötter, Jürgen; Ohm, Agnes (Metropol Verlag, 2021)
The exhibition "Écraser l’infâme!" presents the paintings, prints, and drawings of eight artists from Germany, the Netherlands, Austria, the Czech Republic, and Poland, all of whom were once interned at Oranienburg or Sachsenhausen Concentration Camps. In focus are not only works from the individual’s internment period, but also those from before and after. Until a few years ago, artwork from the concentration camps was viewed only as historical documents with no artistic value, but today, the artist can step out of the inmate’s shadow. The exhibition explores the effects of concentration camp internment on individuals and their artmaking. This catalogue includes colour images of all the artworks exhibited and tells the life stories of the featured artists: Jan Budding, Peter Edel, Hans Grundig, Leo Haas, Vladimír Matêjka, Rudolf Carl Ripper, Viktor Siminski, and Karel Zahrádka.